Topical hyaluronic acid in the management of oral ulcers - Pranav Kapoor; Shabina Sachdeva; Silonie Sachdeva (Wolters Kluwer Medknow Publications, 2011)
Hyaluronic acid is a hygroscopic macromolecule formed by the polymerisation of glucuronic acid and N-acetylglucosamine disaccharide. It is a primary component of the extracellular matrix in various body tissues. Ihe use of topical Hyaluronic acid in the treatment of oral ulcers has been recently reported. This article reviews the mechanism of action, indications and efficacy of topical Hyaluronic acid gel in the management of oral ulcers.